Cold Plasma Inactivation of Escherichia coli O157:H7 Biofilms - Niemira, Brendan A.; Boyd, Glenn; Sites, Joseph (Frontiers in Sustainable Food Systems, 2018)
Pathogenic bacteria associated with biofilms on foods and food contact surfaces are a challenge to inactivate with conventional sanitizers. Cold plasma is a novel nonthermal process with potential efficacy against these pathogens. Biofilms of Escherichia coli O157:H7 were grown for 24, 48 or 72 h on glass slides and exposed to atmospheric cold plasma, 23 kHz to 48 kHz, for 5, 10 or 15 s. Distance from emitter to biofilms was 5 cm or 7.5 cm. The temperature of the process was established using infrared digital imagery. Cold plasma at 5 cm reduced biofilms by up to 1.41, 2.57 or 3.29 log cfu ml-1 for 5, 10 or 15 s, respectively. Cold plasma at 7.5 cm had reduced maximal efficacy at 5 s and 10 s (0.96 and 2.13 log cfu ml-1, respectively), but was unchanged for 15 s (3.29 log cfu ml-1). Biofilm age was not significant factor influenceing cold plasma efficacy. All treatments were confirmed to be non-thermal. Cold plasma can be a sanitizing tool for food contact surfaces.